O racismo religioso estrutural presente no novo ensino médio do currículo paulista: uma análise a partir de dois componentes curriculares - Lima Junior, Antonio Pedro (2024)
This study aimed to analyze the structural religious racism present in two components of the New High School Curriculum of São Paulo. Before delving into the Support Material for Planning and Deepening Practices, we briefly explored myths and their importance in the study of a people's history, art, and culture, to understand the reason for the exclusion of African and Afro-Brazilian mythology from the São Paulo Curriculum and the educational materials sent to schools. We concluded that the most renowned mythologists and scholars of myths advocate for their study and teaching to better understand a people. Next, we analyzed educational legislation and its possible applications, identifying a gap between theory and practice that prevents the implementation of the legislation as it was designed. Finally, we conducted a specific analysis of the materials from the two selected components of the New High School. A more detailed examination of structural religious racism in basic education revealed a concerning gap: the limitation of this issue's approach to the Religious Education curriculum component, excluding other components, especially those of the General Basic Education. The methodology used for this research was content analysis